Effect of calcium-sensing receptor on the migration and proliferation of porcine intestinal epithelial cells. Issue 2 (3rd April 2023) - Zheng, Jie; Liu, Guangmang; Wu, Caimei; Jia, Gang; Zhao, Hua; Chen, Xiaoling; Wang, Jing
Abstract: The rapid healing of impaired intestinal surface plays a role in maintaining intestinal homeostasis. This study investigated the effect of calcium-sensing receptor (CaSR) on the migration and proliferation of intestinal porcine epithelial cells (IPEC-J2). Results showed that cell migration area and width were increased by R568 (CaSR activator) and decreased by NPS2143 (CaSR inhibitor). The protein level of GTP-rac1 and the phosphorylation of phospholipase C gamma 1 (PLCγ1) were increased by 2 µM R568. Furthermore, R568 + 120 µM NSC23766 (Rac1 inhibitor) and R568 + 1 µM U73122 (PLCγ1 inhibitor) decreased the protein level of GTP-rac1 and the phosphorylated PLCγ1, respectively, and both inhibited cell migration compared with R568. In addition, spermine increased the protein expression levels of CaSR and the levels of GTP-rac1 and the phosphorylated PLCγ1 and thereby promoted the migration of IPEC-J2 cells. Moreover, R568 improved the proliferation of the IPEC-J2 cells. Spermine increased cell proliferation, but NPS2143 incubated with spermine decreased cell proliferation compared with the spermine group. This study suggests that CaSR activation increased cell migration by activating Rac1 and PLCγ1 signaling and improved cell proliferation, and both effects were regulated by spermine by activating CaSR.